ANALISA PERSEPSI AKUNTAN TENTANG PENGARUH INTELLECTUAL CAPITAL TERHADAP CUSTOMER SATISFACTION DAN FINANCIAL PERFORMANCE (STUDI KASUS PADA KANTOR AKUNTAN PUBLIK DI SURABAYA) - Septianto, Kenny (Business Accounting Review, 2016)
This study aimed to examine the direct significant affect of intellectual capital to financial performance in public accountant in Surabaya. This study also examined the indirect significant relationship of intellectual capital to financial performance through customerâs satisfaction as intervening variable in public accountant in Surabaya. This study usedÂ  offices quantitative approach, and the data were obtained through distributing questionnaires to public accountant in Surabaya. The data obtained processed by using smartPLS software. This study showed that there was a positive and significant relationship of intellectual capital to customerâs satisfaction; customer satisfactionâs to financial performance; and intellectual capital to financial performance in public accountant offices in Surabaya.